Nonlinear association of physical activity with early cardiovascular-kidney-metabolic syndrome risk: a comprehensive analysis of NHANES data from 2007 to 2018 - Haozhe Wang; Yike Zhang; Meimei Sun; Zhou Chen (BMC Public Health)
Abstract Background Cardiovascular-kidney-metabolic (CKM) syndrome, a newly defined cluster of interrelated cardiometabolic disorders, poses a global health burden. While physical activity (PA) is a cornerstone of metabolic health, its relationship with early CKM progression remains unclear. This study aims to explore the nonlinear dose-response evidence between PA and early CKM syndrome and highlights the potential PA thresholds to maximise metabolic health benefits, providing theoretical support for personalized PA guidelines. Methods Using data from the National Health and Nutrition Examination Survey (NHANES) 2007–2018, we analyzed 12,068 participants with early CKM (stages 0–2). Moderate-to-vigorous physical activity (MVPA) was quantified as metabolic equivalent of task (MET)*min/week. Restricted cubic splines, weighted logistic regression, and mediation analyses were employed to assess MVPA-CKM relationships and mediating roles of obesity-related indicators. Subgroup analyses evaluated heterogeneity across demographics and other core covariates. Results A L-shaped association between MVPA and early CKM risk was identified (p-non-linear < 0.001). Before the lowest point (6872 MET*min/week), any incremental increase in MVPA was associated with a reduction in early CKM risk, and moderate MVPA (600 − 12,600 MET*min/week) exerts a protective effect. Up to the threshold of 12,600 MET*min/week, MVPA continued to exhibit protective effects. The mediating effect of all the obesity-related indicators was not significant (p > 0.05). Protective effects of moderate PA were consistent across the majority subgroups, whereas an attenuation or even reversal of this protective effect was observed at excessive MVPA levels (> 12,600 MET*min/week), where outcomes statistically indistinguishable from those observed at MVPA levels below 600 MET*min/week. Conclusions This study reveals an L-shaped association between MVPA and early CKM risk. The findings highlight the protective effects of moderate MVPA (600 − 12,600 MET*min/week) while demonstrating that higher MVPA (> 12,600 MET*min/week) may attenuate or even reverse these benefits.